VARIÁVEIS MORFOMÉTRICAS E RELAÇÕES INTERDIMENSIONAIS PARA Cordia trichotoma (Vell.) Arráb. ex Steud. - Maína Roman; Delmar Antonio Bressan; Miguel Antão Durlo (Ciência Florestal, 2009)
The present work was developed to observe the morphometric features and the morphometric relations for Cordia trichotoma trees in a planted forest, at Santa Maria municipality, state of RS, Brazil. The analised variables were: total height, comercial height of stem, diameter at breast height (dbh), crown diameter, crown length, crown proportion, crown projection area, slenderness rate, salience index, range index and crown formal. For the interdimensional relations study, the morphometric variables were related to diameter at breast height (dbh), by regression analysis. The results showed significative statistic relations between dbh and variables such as total height, crown diameter, crown length, crown proportion, slenderness rate and range index.